Decision Support for GPs: Towards a more certain future? - Peter Pritchard (Journal of Innovation in Health Informatics, 1995)
General practitioners are expected to make decisions on the problems of every patient whom they see, under conditions of great uncertainty. Pressure for cost containment is growing, and quality of care and accountability are major issues. Medical knowledge of varying relevance is accumulating at an increasing rate, so that GPs find themselves in a quicksand of volatile and unvalidated knowledge. Weighing up all the options, and seeking more information in order to select the favoured option is not easy in the time available. Then there is the burning question whether a decision has benefited an individual patient. The new generation of knowledge-based decision support (KBDS) computer systems may be able to offer some help.